Set of Values of Fractional Ideals of Rings of Algebroid Curves - Guzmán, Edison Marcavillaca Niño de (2018)
The aim of this work is to study rings of algebroid Gorenstein rings. We explore more deeply the symmetry that exists among the sets of values of a fractional ideal and that of its dual and also to express the codimension of a fractional ideal in terms of the maximal points of the value set of the ideal. We apply the formulas we obtained to express the Tjurina number of a complete intersection curve in terms of invariants of its components and the maximal points of the set of values of the Kähler differentials on the curve.